VALUASI EKONOMI KARBON PADA TEGAKAN TINGKAT TIANG DAN POHON DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) HUTAN DIKLAT BUKIT SULIGI KABUPATEN ROKAN HULU - Betani, Anderlef; Sribudiani, Evi; Mukhamadun, Mukhamadun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Global warming occurs becauseit’s energy accepted of sunshine absorbed as short wave radiation and restored in sky as infrared radiation longwave. Be related the phenomenon this climate change, forests have an important role because it can absorb and store carbon.Forest For Special Purpose (KHDTK)Jungle Training Bukit Suligi Regency Rokan Huluhave a level of reserves stored carbon is large enough and have an active role to lower the air temperature and resolve global warming, it is becoming one opportunity for forest status as Trees at Forest For Special Purpose (KHDTK)Jungle Training Bukit Suligiunknown potential economic valuation of carbon stored in it. The result of this research is expected suspect magnitude economic carbon valuation in the stands level poles and Trees at Forest For Special Purpose (KHDTK)Jungle Training Bukit Suligi. The results of this study showed the magnitude valuation carbon economy in the Trees at Forest For Special Purpose (KHDTK)Jungle Training Bukit Suligi the results of carbon 83,957,52 ton. If 1 US =Rp 13.425,00 It can be appreciated US 419.787,6 or Rp 5.635.648.530Keywords: KHDTK Bukit Suligi, Forest, economiccarbon